Monte Carlo simulations of nuclear processes during solar flares in a magneto active plasma - Serra, Jordi Tuneu (2021)
Solar flares are explosive phenomena involving the energy release of 1027 to 1032 erg in the solar atmosphere in tens of seconds to tens of minutes, manifested as emission of radiation nearly over the entire electromagnetic spectrum, sometimes associated with mass motions involving the escape of energetic particles. We do not yet completely understand the precise mechanisms by which energy is stored in the magnetic field loops above active regions and suddenly released. Moreover, we do not fully understand the mechanism that accelerates particles. Nonetheless, we know that magnetic reconnection in tenuous plasmas plays a key role. Monte Carlo simulations including magnetic fields become computationally impractical in the solar flare context since the length of the magnetic loops, thousands of km, is several orders of magnitude larger than the gyroradius of the particles involved, from cm to m depending on the particle species and the magnetic field strength. To address this problem we have written a new module for the Geant4 package using the Guiding Centre (GC) approach, in which the particle motion is averaged over a gyrofrequency. We describe the formulation and implementation of this method, in particular dealing with the uncertainty in the gyrophase so that particle velocities are well-defined for input to the Geant4 modules handling reactions. The modelling of secondary particle production by energetic ions in the presence of magnetic fields within the GC approach, which allows to reduce the runtime of simulations from two to five orders of magnitude compared to the standard Newton-Lorentz approach, will provide a framework for interpreting the detailed observations expected from leading-edge instruments such as ALMA and LLAMA, as well as existing gammaray measurements from the Fermi satellite and earlier experiments.